1997
DOI: 10.1177/026361749701500902
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Various Factors on the Sorption of Endosulphan on Two Indian Soils

Abstract: The effects of exchangeable cations (H+ and Na+), organic matter, non-ionic and anionic surfactants, and temperature on the sorption of endosulphan on two different types of soils were studied. Adsorption studies were performed using the batch technique and adsorption isotherms for all effects/treatments were in close agreement with the Freundlich equation. The adsorptive capacity of endosulphan towards organic matter and clay content in the natural forms of both soils was also evaluated by calculating the cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2006
2006
2008
2008

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 19 publications
2
3
0
Order By: Relevance
“…Sorption isotherms of α‐endosulfan by kaolinite in the presence of HA are compared with those in the absence of HA in Figure 2a. The K f values obtained from this experiment (Table 3) agree well with previous studies, which reported that the sorptive K f values of α‐endosulfan ranged from 6.74 to 140.7 ml/g in soils with low organic matter content [22,23,24,26]. The values of K f for α‐endosulfan by kaolinite in the presence of HA were approximately 1.3 times greater than those for the kaolinite‐only system, suggesting additional sorption of α‐endosulfan onto HA covering the surface of solids.…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…Sorption isotherms of α‐endosulfan by kaolinite in the presence of HA are compared with those in the absence of HA in Figure 2a. The K f values obtained from this experiment (Table 3) agree well with previous studies, which reported that the sorptive K f values of α‐endosulfan ranged from 6.74 to 140.7 ml/g in soils with low organic matter content [22,23,24,26]. The values of K f for α‐endosulfan by kaolinite in the presence of HA were approximately 1.3 times greater than those for the kaolinite‐only system, suggesting additional sorption of α‐endosulfan onto HA covering the surface of solids.…”
Section: Resultssupporting
confidence: 88%
“…Sorption isotherms of ␣-endosulfan by kaolinite in the presence of HA are compared with those in the absence of HA in Figure 2a. The K f values obtained from this experiment ( Table 3) agree well with previous studies, which reported that the sorptive K f values of ␣-endosulfan ranged from 6.74 to 140.7 ml/g in soils with low organic matter content [22,23,24,26].…”
Section: Sorption Of ␣-Endosulfan By Minerals With Ha Presentsupporting
confidence: 90%
See 2 more Smart Citations
“…Most of the data on pesticide adsorption by soils deals with aqueous solutions [3][4][5][6]. However, a number of investigations have been carried out on the adsorption of pesticides on soils from non-aqueous solvents and solvent mixtures [6][7][8][9][10] and it was reported that the adsorption capacity for pesticides decreased with the increase of the volume fraction of the organic solvent [11]. On the other hand, the adsorption of pesticides from water may be suppressed by the hydrophilic nature of soil which increased the adsorption of water rather than of the pesticide [12].…”
Section: Introductionmentioning
confidence: 99%